Effect Of Administration Of Sodium Cyclate (C6h12nnao3s) On The Number Of Polymorfonuclear Cells (PMN) In Rats (Rattus Norvegicus) - Rahmadani Ayu Nugraheni (Jurnal Biosains Pascasarjana, 2022)
Cyclamate is one of the artificial sweeteners that is still often consumed by the public as a food or beverage additive. In some countries, cyclamate is prohibited for consumption because it is carcinogenic. This study was conducted to determine the effect of sodium cyclamate on the number of polymorphonuclear cells (PMN). The type of research used was a laboratory experimental. The sample used was a male rat totaled of 25 which were divided into 5 treatment groups which was without sodium cyclamate, administered sodium cyclamate at a dose of 4.5 mg / 200 g BW, administered sodium cyclamate at a dose of 9.5 mg / 200 g BW, administered sodium cyclamate at a dose of 14.5 mg / 200 g BW, and administered sodium cyclamate at a dose of 19, 5 mg / 200 g BW. The research finding revealed the statistical significancy for p<0.05 indicated that there was an effect of sodium cyclamate to the number of polymorphonuclear cells. The usage of sodium cyclamate is known to generate oxidative stress, which results in cell damage and leukocytosis.